The Effect of Compensation, Work Discipline and Work Safety on Employee Performance at PT Megah Bevel Duren Sawit East Jakarta - Gina Alia (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study expects to decide the impact of remuneration, work discipline, and work wellbeing factors on representative execution at PT. Megah Slope Duren Sawit, either or at the same time. Information assortment was done by appropriating surveys, research conducted on 50 respondents, a sample of all employees of PT. Megah Bevel Duren Sawit. By utilizing scale likert, respondents' responses were handled with legitimacy and dependability tests, old style supposition test, numerous relapse examination, t test, F test and R2 tests. The results showed that all data tested were valid and reliable and found that partial compensation (X1) and work discipline (X2) had a positive and significant influence on an employee performance, but the variable (X2) was greater in significant than the variable (X1). And found the work safety variable (X3) has a negative and insignificant influence on employee performance